Modulation of the biological network of lumbar spinal stenosis by Tongdu Huoxue Decoction based on clinical metabolomics - Ji, Luhong; Huang, Ping; Wang, Qiong; Li, Xugui; Li, Ying (Frontiers in Molecular Biosciences, 2023)
Objective: To explore the clinical efficacy and metabolic mechanism of Tongdu Huoxue Decoction (THD) in treating lumbar spinal stenosis (LSS). Methods: A total of 40 LSS patients and 20 healthy participants were recruited from January 2022 to June 2022. The patients’ pre- and post-treatment visual analogue scale (VAS) and Japanese Orthopaedic Association (JOA) scores were recorded. ELISA kits were used to assess pre- and post-treatment levels of serum Interleukin-1beta (IL-1β), Alpha tumour necrosis factor (TNF-α) and prostaglandin E2 (PGE2). Finally, the patients’ pre- and post-treatment and healthy human sera were subjected to extensively targeted metabolomics using Ultra Performance Liquid Chromatography (UPLC) to identify potential differential metabolites and metabolic pathways using multivariate statistical analysis. Results: Compared to the pre-treatment (group A), the patients’ VAS scores decreased significantly (p < 0.05), while JOA scores increased significantly (p < 0.05) post-treatment (group B), indicating that THD could effectively improve the pain and lumbar spine function of LSS patients. Moreover, THD could effectively inhibit the expression of IL-1β, TNF-α and PGE2-associated inflammatory factors in serum. Regarding metabolomics, the levels of 41 differential metabolites were significantly different in the normal group (group NC) compared to group A, and those were significantly restored after treatment with THD, including chenodeoxycholic acid 3-sulfate, taurohyodeoxycholic acid, 3,5-Dihydroxy-4-methoxybenzoic acid, pinocembrin. These biomarkers are mainly involved in purine metabolism, steroid hormone biosynthesis and amino acid metabolism. Conclusion: This clinical trial demonstrated that THD is effective in improving pain, lumbar spine function and serum levels of inflammation in patients with LSS. Moreover, its mechanism of action is related to the regulation of purine metabolism, steroid hormone biosynthesis and the expression of key biomarkers in the metabolic pathway of amino acid metabolism.